Design, Synthesis and Biological Evaluation of Hydroxamic Acid Derivatives as Potential High Density Lipoprotein (HDL) Receptor CLA-1 Up-Regulating Agents - Yu Du; Yanbin Wu; Bin Hong; Yuan Yang; Xiaojian Jia; Li Wang; Xiaofang Chen (Molecules, 2011)
Trichostatin A (TSA) and suberoylanilide hydroxamic acid (SAHA) were reported in our recent publication as novel human high density lipoprotein (HDL) receptor CD36 and Lysosomal integral membrane protein-II Analogous-1 (CLA-1) up-regulators. As part of a broader effort to more fully explore the structure-activity relationships (SAR) of CLA-1 up-regulators, we synthesized a series of hydroxamic acid derivatives and evaluated their CLA-1 up-regulating activities in HepG2 cells. Some compounds exhibited over 10-fold up-regulation of CLA-1 expression in HepG2 cells at 10 μg/mL concentration. The compound 1g showed the best potency, with a lower EC50 than TSA (EC50 = 0.32 μM versus 1.2 μM). These compounds provide early new CLA-1 up-regulators with potential for treating atherosclerosis.